The molecular identification of airborne bacteria in Basrah, IRAQ - Daood, Nisreen Wasmi; Al-Hamdani, Maytham A. (Iraqi Journal of Science, 2025)
The objective of this study is to elucidate the environmental significance and potential health implications of airborne microorganisms through their molecular characterization, thereby enhancing our comprehension of atmospheric health and its broader impact on human well-being. Amplification of the 16sRNA gene was carried out based on the multiplex polymerase reaction and used Sanger method determining the nucleotide sequence of DNA to determine the evolutionary relationships, as it is a clear and reliable diagnostic method instead of the traditional inaccurate methods. The study included five stations from Basra Governorate, Iraq, represented by the areas of Qurna, Shuaiba, Tanumah, Khor Al-Zubair and Old Basra, as it revealed The study covers five genera belonging to 16 Gram-negative and Gram-positive bacteria species: Mammliicoccus lentus, Staphylococcus saprophyticus, Erwinia, Staphylococcus hominis, Lysinibacillus, Exiguobacterium aurantiacum, Staphylococcus epidermidis, Staphylococcus equorum, Staphylococcus succinus, Bacillus pumilus, Bacillus safensis, Staphylococcus xylosus, Pseudomonas aeruginosa, Atlantibacter hermannii, Bacillus subtilis, and Pantoea agglomerans). The isolated bacteria were submitted to the NCBI GenBank database for registration. Using the MEGA 11 software, a phylogenetic tree was constructed to analyze the evolutionary relationships among the study isolates and compare them to internationally available samples.